PENGARUH PENGETAHUAN DAN KONSUMSI OAINS TERHADAP KEJADIAN GASTRITIS DI KABUPATEN ENDE - Bai, Marieta; Cahyani, Sisilia L.; Doondori, Anatolia K.; Sekunda, Maria S. (Kelimutu Nursing Journal, 2023)
Gastritis is a non-communicable disease which is still a global health problem. The level of awareness of the Indonesian people to maintain stomach health, especially gastritis is still low, so because of low public awareness, it is often left alone without treatment. The aim of the study was to identify the effect of knowledge and consumption of NSAIDs on the incidence of gastritis in Ende district. The design used was analytic observation using a case control design. Data was collected in August 2017 using a questionnaire. Data were analysed multivariately using logistic regression. The place/location where the case study was conducted was in Ende district. The results showed that cases and controls were comparable in terms of gender (p=0.224), age (p=0.360), education (p=0.001) and occupation (p=0.430). The results of the multivariate test showed that the habit of consuming NSAIDs (OR 5.159; p = 0.003), and knowledge about gastritis (OR 7.945; p = 0.000). It can be concluded that knowledge and consumption habits of NSAIDs are one of the factors causing gastritis in Ende Regency. Therefore, promotive efforts are needed in the form of counselling about Gastritis and the habit of not taking NSAIDs without a doctor's prescription.